Extensional Tectonic Regime of Garut Basin based on Magnetotelluric Analysis - Lina Handayani; Kamtono Kamtono; D. D. Wardhana (Geological Agency, 2013)
DOI: 10.17014/ijog.v8i3.162Garut Basin are is part of Bandung-Garut Greater Basin (Bandung Zone) characterized by a large basin surrounded by mountain ranges. Active volcanoes had distributed their material as pyroclastic deposits around the outer border of the zone and as lava flow deposit separating the two basins. Bouguer gravity anomaly data had also indicated the presence of several low anomaly closures at about the area of Bandung and Garut Basins that were surrounded by high gravity anomaly zones. Two magnetotelluric surveys were completed to acquire the subsurface model that might explain the tectonic evolution of studied area. The first stage was characterized sby the presence of horst - graben structures that might imply an extensional regime of the area. The next stage of evolutionwas indicated by the horizontal layering correlated to the relative non-active tectonic. In addition, a most recent structure that appeared near the surface might suggest a possible extension force as the current stage.